2012
DOI: 10.1021/jp210082f
|View full text |Cite
|
Sign up to set email alerts
|

Ion Exchange in Metal–Organic Framework for Water Purification: Insight from Molecular Simulation

Abstract: A molecular simulation study is reported for ion exchange in a rho zeolite-like metal–organic framework (ZMOF). The nonframework Na+ ions in rho-ZMOF are observed to exchange with Pb2+ ions in PbCl2 solution. At equilibrium, all Pb2+ ions are exchanged and reside in rho-ZMOF, while Na+ ions are in a dynamic equilibrium with solution. By umbrella sampling, the potential of mean force for Pb2+ moving from solution into rho-ZMOF is estimated to be −10k B T, which is more favorable than −5k B T for Na+ and contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 34 publications
0
51
0
2
Order By: Relevance
“…O aumento da população mundial e o desenvolvimento econômico introduziu uma enorme quantidade de contaminantes, como os íons metálicos [1]. A não remoção de metais de efluentes pode causar danos tanto à saúde humana quanto à indústria, pois metais como cálcio e magnésio são associados à dureza da água [2].…”
Section: Introductionunclassified
“…O aumento da população mundial e o desenvolvimento econômico introduziu uma enorme quantidade de contaminantes, como os íons metálicos [1]. A não remoção de metais de efluentes pode causar danos tanto à saúde humana quanto à indústria, pois metais como cálcio e magnésio são associados à dureza da água [2].…”
Section: Introductionunclassified
“…97 As the next example, an anionic nanoporous framework material with mobile guest cations [HDMA] 3 [(Cu 4 Cl) 3 -(btc) 8 ]$ 9DMA (43) has been reported. This MOF can perform ionexchange with tetraalkylammonium cations, such as TMA (44), TEA (45) or TPA (46). The research group also indicated that cation-exchange within this anionic framework creates unusual pore partition effects on gas separation (CO 2 /N 2 ).…”
Section: àmentioning
confidence: 99%
“…Most inorganic ionexchanges occur in small pore sizes and thus, the kinetics of the ion-exchange is slow, though organic exchangers, such as polymer resins, display rapid ion-exchange. 44 In the other aspect, ion-exchange can be divided into cationexchange and anion-exchange. This study outlines the available observations of all types of exchange that occurs in the pores of MOFs and the general trends and future studies can be outlined.…”
Section: Introductionmentioning
confidence: 99%
“…It is self-assembled by noncovalent forces involving hydrogen bonding, coordinating bonds, aromatic p-stacking interactions, electrostatic and charge-transfer attractions [1]. Supramolecular assembly is a central theme in the design of new solid state structures with unusual conductance, gas storage, ion exchange, luminescence, catalysis, electrooptic or magnetic properties [2][3][4][5][6][7][8]. Interest has been focused on supramolecular networks constructed from hydrogen bonds and pÁÁÁp stacking interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Crystal data and structure refinement parameters for complexes[1][2][3][4] is 228 cm -1 , which indicates the presence of monodentate coordination mode in 1-3. The IR spectrum of the complex 4 shows a wide band with a peak at 3,359 cm -1 is attributed to the O-H stretching vibrations.…”
mentioning
confidence: 97%